Assessing BIT alumni: Determinants of success in the workplace as perceived by the employers - Jamaludin, Zulikha; Abdul Mutalib, Ariffin; Azzali, Fazli; Mohamed Elias, Ezanee (Universiti Utara Malaysia, 2005)
As the pioneer in offering the BIT degree programme in Malaysia and having conducted the course for the past 15 years, it is incumbent upon the Faculty of Information Technology UUM to investigate whether or not it is producing graduates who meet the needs of the job market. The BIT program has been revised a few times.However the revisions were done without any formal evaluation on the product, i.e. the BIT graduates.Revisions by the academia within the faculty are inadequate without being complemented by employer assessment.Views from the employers are important to ensure that the BIT curriculum meets current needs of industry.These days, being a knowledgeable graduate is not adequate if the knowledge possessed is irrelevant to the organisations concerned. This study was carried out with the realization that such a situation existed.. We tried the most appropriate method, as confirmed by the literature, to find out the types of knowledge and skills needed by the employers from our graduates as they compared the graduates’ knowledge and skills with a perceived importance level.Knowledge and skills were divided into 19 attributes, which were used by the employers to rate the knowledge, skills and importance levels.Obtaining the measures, we calculated the knowledge gap and performance gap for each attribute so as to enable us to identify the most critical knowledge and skills needed by the organisations.With such information, we can identify our strengths and weaknesses, which we used as a basis to propose ways for improving our BIT curriculum that would neither sacrifice the requirements of the knowledge epistimology nor the need of the organisations.This study reveals interesting, yet challenging findings.The employers see project management and communication skills (verbal and written) as the top most important ability that must be mastered by our BIT graduates.Other details of the finding and analysis are further described in this report.